2016
DOI: 10.1007/s10439-016-1760-x
|View full text |Cite|
|
Sign up to set email alerts
|

Designing 3-Dimensional In Vitro Oviduct Culture Systems to Study Mammalian Fertilization and Embryo Production

Abstract: The oviduct was long considered a largely passive conduit for gametes and embryos. However, an increasing number of studies into oviduct physiology have demonstrated that it specifically and significantly influences gamete interaction, fertilization and early embryo development. While oviduct epithelial cell (OEC) function has been examined during maintenance in conventional tissue culture dishes, cells seeded into these two-dimensional (2-D) conditions suffer a rapid loss of differentiated OEC characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 117 publications
(179 reference statements)
1
32
0
Order By: Relevance
“…This implies that sperm‐oviduct interactions and the presence of bioactive components in the oviduct fluid are able to suppress polyspermy. For this reason, we are establishing an oviduct‐on‐chip system for the pig, similar to what we made for the cow (Ferraz et al, ; Ferraz, Henning, Stout, Vos, & Gadella, ) and the mare (Leemans et al, ), in order to develop a better mimic of the oviduct. This will ultimately produce better embryos as well as reduce polyspermic fertilization and the incidence of parthenogenic activation.…”
Section: The Journeymentioning
confidence: 99%
“…This implies that sperm‐oviduct interactions and the presence of bioactive components in the oviduct fluid are able to suppress polyspermy. For this reason, we are establishing an oviduct‐on‐chip system for the pig, similar to what we made for the cow (Ferraz et al, ; Ferraz, Henning, Stout, Vos, & Gadella, ) and the mare (Leemans et al, ), in order to develop a better mimic of the oviduct. This will ultimately produce better embryos as well as reduce polyspermic fertilization and the incidence of parthenogenic activation.…”
Section: The Journeymentioning
confidence: 99%
“…The oviduct fluid microenvironment is composed of plethora of growth stimulatory factors, immunomodulatory components and extracellular-vesicles/exosomes (Exo), which all are known to play an important role during a series of crucial reproductive events [ 1 , 2 , 3 ]. The oviduct epithelium contains the population of several ciliated and secretory cells that makes the oviduct fluid, which influences the whole journey from embryonic development into a successful adult [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of 3D printed microfluidic devices for organs-on-chip applications remains relatively under-explored. To date, a number of studies have already demonstrated the successful implementation of 3D printed microfluidic devices coupled with bioprinted [14][15][16][17][18][19][20] or photopatterned cell-laden hydrogels [21]. While this approach can recreate a 3D environment by supporting cells with synthetic or natural extracellular matrices and provide a means to probe cell-matrix interactions, it is limited in recapitulating multicellular interactions and organization, which is highly relevant to physiologically cell-dense tissues, such as tumors and hepatic tissues.…”
Section: Introductionmentioning
confidence: 99%